Language learning strategies of Vietnamese EFL students and their correlation with learning experience and language anxiety. - Pham, Thu Thao (2017)
In general, exploring the strategy use of good language learners and its influenced factors seems to be highly practical for pedagogical strategy training. However, knowing the learning strategy of less proficient learners may also be useful in order to identify the fail rationale and cast light on the differences between two groups. A mixed method approach was used in this dissertation to investigate the language learning strategies (LLSs) of the non-English major students in a university in the North of Vietnam. The study also explores whether previous learning experience and language anxiety impact on the choice of LLS. The study found that Vietnamese EFL students were medium strategy users. A comparison of the disparity in LLS utilisation generally revealed that the more successful students used strategies more frequently than the less successful learners, with the exception of memory and compensation strategies. The degree of memory strategy use of both groups was found to be at medium-use range, whilst the higher effective students employed moderately less compensation strategies than their lower effective peers. Moreover, whilst interplay may exist between LLS utilisation and previous language learning experience, there is no relationship between the overall use of LLS and language anxiety.